2003
DOI: 10.1021/ie020951g
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Reactive Dye Solutions by Electrocoagulation Using Aluminum Electrodes

Abstract: The removal of pollutants from effluents by electrocoagulation has become an attractive method in recent years. This paper deals with the batch removal of the reactive textile dye Remazol Red RB 133 from an aqueous medium by the electrocoagulation method using aluminum electrodes. The effects of wastewater conductivity, initial pH, current density, stirring rate, dye concentration, and treatment time on the decolorization efficiency and energy consumption have been investigated. Aluminum hydroxypolymeric speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(183 citation statements)
references
References 29 publications
8
171
0
4
Order By: Relevance
“…Lung Chou et al [20] have indicated that an excess amount of NaCl in the solution is detrimental to removal of turbidity. The present trend is in agreement with the work of Can et al [21]. However; Emamjomeh and Sivakumar [22] and Merzouk et al [23] showed a trend in contrast to the present work.…”
Section: Effect Of Electrolysis Timesupporting
confidence: 92%
“…Lung Chou et al [20] have indicated that an excess amount of NaCl in the solution is detrimental to removal of turbidity. The present trend is in agreement with the work of Can et al [21]. However; Emamjomeh and Sivakumar [22] and Merzouk et al [23] showed a trend in contrast to the present work.…”
Section: Effect Of Electrolysis Timesupporting
confidence: 92%
“…Aluminium ions generated during electrochemical processes of manganese removal may form monomeric species such as Al(OH) 2+ [50]. Average concentration of aluminium, immediately after 20 min of composite interaction with Mn 2+ synthetic waters, was 0.2131 mg/dm 3 and included all mentioned monomeric and polymeric species which were not coagulated.…”
Section: Interaction Of Composite Materials With Ionic and Colloidal Fmentioning
confidence: 99%
“…Plusieurs études ont ainsi montré la possibilité de décolorer efficacement les eaux usées par utilisation de l'électrocoagulation avec des électrodes d'aluminium (AHLAwAT et al, 2008;CAN et al, 2003;MERzOUk et al, 2009) ou de fer (ARSLAN-ALATON et al, 2008;kABDASLi et al, 2009;PALACiO et al, 2009).…”
Section: Introductionunclassified